Trends in lymphomas incidence and mortality in Cuba - Garcia, Antonio Martin (2022)
Background: In Cuba, Limphomas have traditionally been included among the major câncer sites. Objectives: The behavior of incidence and mortality of the lymphomas between 1976 and 1990 is described according to the main epidemiological variables: age, sex and histology. Methods: All cases reported as lymphomas to the National Câncer Registry between 1976 and 1990 were included. Cases were grouped in the two classic diagnostic categories: Hodgkin ’s disease and non-Hodgkin Lymphomas and, according to the moment of the reporting, in three five-year periods. Age-specific rates and age standardized rates were calculated. Results: Na elevated male predominance was found in both diagnostic categories for incidence and mortality. Incidence, both in Hodgkin’s disease and non-Hodgkin Lymphomas, has hadan ascending behaviour in this period. Increasing trends in incidence and mortality are noticeable for children (0-14 years).